Inovasi di Era Disrupsi - Muhammad Iqbal Iqbal (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2022)
Once when transition happens, we will always find a group of people who are not ready and resist change. Unemployment becomes inevitable. However, the transition period also made people start thinking about the importance of skills. This is innovation in the era of disruption, these changes are the impact of the increasingly rapid development of science and technology, which in turn shapes the characteristics of educational institutions to be competent, beating one another. So there is no place in educational institutions without competition.